Fathoming the impact of covid-19 on education in Nigeria (Multi-disciplinary Journal of Research and Development Perspectives, 2026)
The paper concerns itself with fathoming the impact of COVID-19 on education in Nigeria. The disease outbreak which occurred in Wuhan City, Hubei Province, China spread to other parts of China and indeed to several countries killing thousands of people. The disease eventually spread to Nigeria and due to the deadly nature of the virus, the government came up with the policy of social distancing leading to the closure of societal institutions such as schools, markets, motor parks etc. This abrupt closure of schools as a measure of containing the COVID-19 pandemic no doubt has made some impact on education in Nigeria. For instance, it was found that in the lower level of education, second term examinations were written abruptly and some subjects were not written due to the governments executive order to close schools; the academic calendar has been altered; proprietors of private schools may not find it easy to pay their teachers' salaries duringthe period when COVID-19 is ravaging; Also apart from classroom activities of teaching and learning, other academic exercises such as researches, conferences, workshops, symposia as well as other extra-curricular activities such as school inter house sports, matriculation andconvocation ceremonies are put on hold. Besides, renowned examination bodies such as the West African Examinations Council (WAEC) and the National Examinations Council (NECO) have postponed their earlier scheduled examinations. The Federal Government had also introduced the learn-from-home education broadcast on national radios and national televisions due to the pandemic. To this end, it was recommended among other things that when the pandemic is contained, all the schools should continue what they could not finish in the previous term; the N150 billion earmarked by the Central Bank of Nigeria for small and medium Enterprises should be extended to school proprietors; the learn-from-home education broadcst should be sustained.
Keywords: Impact; COVID-19; Education; Nigeria